Pengaruh Pembelajaran Kolaboratif terhadap Kemampuan Berpikir Kritis Siswa pada Materi Pembagian Di Kelas IV SDN Padelegan 1 Pamekasan - Sulistiawati, Yuni; Wulandari, Rika (Yayasan Arrahman Nahdlatul Wathan, 2024)
The purpose of this research is to determine whether there is a significant influence of collaborative learning on students' critical thinking skills in division material in Grade IV of elementary school Padelegan 1 Pamekasan. This type of research is a Quasi-Experimental design with a Nonequivalent Control Group. The population of the study is all students in Grade IV of elementary school Padelegan 1 Pamekasan. The Sampling technique used is Simple Random Sampling, with a sample size of 54 students. This research uses an experimental class and a control class. Data collection techniques include interviews, critical thinking ability tests, observation of the implementation of learning, and documentation. The test items for critical thinking ability were evaluated for validity, reliability, difficulty level, and distinguishing power. The data analysis technique involves prerequisite tests using normality and homogeneity test, while hypothesis testi using independent sample t-test. Based on the data analysis result from the independent sample t-test, a Sig. (2-tailed) value of 0.000 < 0.05 and ttest > ttable results of 5.522 > 2.007 indicate that H0 is rejected and Ha is accepted. Therefore, can be concluded that there is a significant influence of collaborative learning on students' critical thinking skills regarding division material in Grade IV of elementary school Padelegan 1 Pamekasan.